2004
DOI: 10.1016/j.cell.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Two Enzymes in One

Abstract: Although a great deal is known biochemically about peroxiredoxins (Prxs), little is known about their real physiological function. We show here that two cytosolic yeast Prxs, cPrxI and II, which display diversity in structure and apparent molecular weights (MW), can act alternatively as peroxidases and molecular chaperones. The peroxidase function predominates in the lower MW forms, whereas the chaperone function predominates in the higher MW complexes. Oxidative stress and heat shock exposure of yeasts causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
358
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 681 publications
(380 citation statements)
references
References 36 publications
20
358
2
Order By: Relevance
“…The catalytic sites contain Cys-49 and Cys-169 in the conserved tripeptide Val-Cys-Pro (VCP) and form an intramolecular disulfide bond essential for the catalytic activity (21,27,28). When we compared these two AhpC proteins, their amino acid sequences were found to be almost identical, with only one point mutation, at residue 101, valine in the HD30 strain and methionine in the HC28 strain (data not shown).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The catalytic sites contain Cys-49 and Cys-169 in the conserved tripeptide Val-Cys-Pro (VCP) and form an intramolecular disulfide bond essential for the catalytic activity (21,27,28). When we compared these two AhpC proteins, their amino acid sequences were found to be almost identical, with only one point mutation, at residue 101, valine in the HD30 strain and methionine in the HC28 strain (data not shown).…”
Section: Resultsmentioning
confidence: 88%
“…Several functional studies of H. pylori AhpC have shown that the AhpCdeleted mutants have increased sensitivity to oxygen (15), overexpress neutrophil-activating protein (18), and accelerate inactivation of catalase (25). As a member of 2-Cys peroxiredoxins (17,21,31), AhpC has been shown to be Trx-dependent (17,27,32,33). The native structure of AhpC in S. typhimurium was shown to exist as a dimer (34,35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon peroxidatic Cys oxidation, 2‐Cys PRDX1 is structurally converted from a peroxidase enzyme to a molecular chaperone under stress conditions 9, 10. In addition to its peroxidase and chaperone functions, PRDX1 could also enhance natural killer cell cytotoxicity and suppress oncogenic proteins such as c‐Myc and c‐Abl 11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%